2015
DOI: 10.4313/teem.2015.16.6.351
|View full text |Cite
|
Sign up to set email alerts
|

Highly Thermal Conductive Alumina Plate/Epoxy Composite for Electronic Packaging

Abstract: In this study, alumina plates 9~25 μm in size were used as thermal fillers, and epoxy resin was used as a polymer matrix. Oriented alumina plate/epoxy composites were prepared using a rolling method. The effect of ordering alumina plates increased with alumina plate size. The thermal conductivity and flexural strength of the composites were investigated. The horizontal thermal conductivity of the oriented composite was significantly higher than the vertical thermal conductivity. The horizontal thermal conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…In this context, the addition of an inorganic filler into an EP matrix to form effective composites is a potential route to improve the performance of the final product. For this purpose, many types of inorganic or metallic fillers with high thermal conductivity, low thermal expansion coefficient, and low electrical conductivity, such as silica [5,6,7,8,9,10], alumina (Al 2 O 3 ) [11,12,13,14], aluminum nitride [15,16,17,18], and hexagonal boron nitride (BN) [19,20,21,22,23,24,25] were studied. Model predictions of and experimental studies on the effects of graphite or graphene oxide on EP resins were also reported [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the addition of an inorganic filler into an EP matrix to form effective composites is a potential route to improve the performance of the final product. For this purpose, many types of inorganic or metallic fillers with high thermal conductivity, low thermal expansion coefficient, and low electrical conductivity, such as silica [5,6,7,8,9,10], alumina (Al 2 O 3 ) [11,12,13,14], aluminum nitride [15,16,17,18], and hexagonal boron nitride (BN) [19,20,21,22,23,24,25] were studied. Model predictions of and experimental studies on the effects of graphite or graphene oxide on EP resins were also reported [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…To further increase the thermal conductive properties with satisfactory processing of electronic packaging materials, the combination of different fillers to obtain a perfect thermal conductive network attracted much interest [29,30,31,32,33,34,35,36,37,38]. The use of Al 2 O 3 particles to reinforce the EP matrix is principally preferred because of its low cost, good thermal stability, corrosive resistance, low thermal expansion, and non-electrical conductivity [11,12,13,14,31,32]. Recently, BN platelets emerged as an outstanding candidate for application to EP-based packaging composite materials because of their unique thermal conductive properties [39].…”
Section: Introductionmentioning
confidence: 99%
“…Although nitride fillers possess a higher thermal conductivity than oxide fillers, their expensive prices are not suitable for practical applications, while Al2O3 has been widely studied because of its high cost performance and rich natural resources [13,14]. However, adding Al2O3 to achieve high thermal conductivity generally requires a high loading [15,16], which will inevitably cause the following problems: firstly, more filler-matrix interfaces are formed in the composite system, leading to high interfacial thermal resistance due to strong phonon scattering and lower overall thermal conductivity of the material [17]; secondly, the excessive introduction of the second phase produces a large number of defects in the matrix, resulting in an increase in system viscosity and a decrease in mechanical properties [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of platelets normal to the crack surface would result in considerable improvement in fracture toughness and stiffness by emanating of two tail lines from the platelet sites and delaying the crack propagation by pinning and crack bridging [3]. To improve the thermal conductivity, a perfectly connected thermo conductive network is formed as an efficient phonon path in organic-inorganic composite materials with plate-like morphology fillers, other than those with spherical ones [5][6][7].…”
mentioning
confidence: 99%